Uji Antioksidan Ekstrak Etanol Buah Asam Jawa (Tamarindus indica L.) Tua dan Muda dengan Metode DPPH - Dwi Kartika Risfanty; Irna Ii Sanuriza (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2021)
One of the biggest causes of death in the world is degenerative diseases, even in Indonesia which increases annually. Some kind of degenerative disease rank in the top 10 among them: heart disease, uric acid, diabetes mellitus, hypertension and others require hospitalization or hospitalization outpatient treatment at a hospital or medical center, also results premature aging due to a decline in collagen and elastic growth free radicalized skin. The disease is not contagious but chronic because of cellular dysfunction and organs. The cause is free radicals and also affected by lifestyle. Preventing the negative effects of free radicals with antioxidant compounds and tamarind fruits contain compounds The antioxidants. The aim of this study is to test activities Antioxidants on the tamarind fruits are young and old, after all comparing the results of both. Methods is used in this research is a DPPH method of testing to find out how high antioxidal activity tamarind fruits young and old. The test results of antioxidant activity young and old tamarind fruit indicates that old Javanese acid has the higher antioxidal activity is 85.28, while the fruit young javanese acid 78.87%. Keywords: antioxidal activit, free radicals, degenerative disease dan DPPH.